2014
DOI: 10.18632/oncotarget.2314
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of STAT3 signaling targets both tumor-initiating and differentiated cell populations in prostate cancer

Abstract: Despite of tremendous research efforts to profile prostate cancer, the genetic alterations and biological processes that correlate with disease progression remain partially elusive. In this study we show that the STAT3 small molecule inhibitor Stattic caused S-phase accumulation at low-dose levels and led to massive apoptosis at a relatively high-dose level in prostate cancer cells. STAT3 knockdown led to the disruption of the microvascular niche which tumor-initiating cells (TICs) and non-tumor initiating cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 38 publications
3
43
1
3
Order By: Relevance
“…Here, our data show that in the absence of SOCS1, STAT3, but not STAT1, is highly activated via phosphorylation. Further, treatment of mice with a STAT3 blocking peptide, STATTIC (39,64,65), reduces both mortality and bacterial burden in iKIR-treated septic mice. STAT3 is activated by IL-6 (66).…”
Section: Discussionmentioning
confidence: 99%
“…Here, our data show that in the absence of SOCS1, STAT3, but not STAT1, is highly activated via phosphorylation. Further, treatment of mice with a STAT3 blocking peptide, STATTIC (39,64,65), reduces both mortality and bacterial burden in iKIR-treated septic mice. STAT3 is activated by IL-6 (66).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms of oesophageal cancer growth and metastasis are not fully understood, which impedes the development of effective treatments. Studies have demonstrated the STAT3 signalling pathway plays a key role in carcinogenesis by promoting cancer proliferation and inhibition of apoptosis . STAT3 exists in a latent form in the cytoplasm but is activated by a wide variety of cell surface receptors via tyrosine phosphorylation to form dimers and translocate into the nucleus, where it binds to STAT‐specific DNA response elements on the promoters of a number of oncogenes such as cyclin B1, c‐Myc, Bcl‐2, P53 .…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated STAT3 dimerizes and translocates into the nucleus to bind to specific DNA response elements to induce the transcription of downstream genes, such as BCL-xL, MCL1 and c-Myc (32). Targeting STAT3 signaling results in suppression of the proliferation of various cancer cells in vitro and tumorigenicity in vivo (33,34). Therefore, the identification and development of novel drugs targeting deregulated STAT3 activation effectively remains an important scientific and clinical challenge (35,36).…”
Section: Discussionmentioning
confidence: 99%